2020
DOI: 10.1098/rspb.2019.2713
|View full text |Cite
|
Sign up to set email alerts
|

Developmental programming of mitochondrial biology: a conceptual framework and review

Abstract: Research on mechanisms underlying the phenomenon of developmental programming of health and disease has focused primarily on processes that are specific to cell types, organs and phenotypes of interest. However, the observation that exposure to suboptimal or adverse developmental conditions concomitantly influences a broad range of phenotypes suggests that these exposures may additionally exert effects through cellular mechanisms that are common, or shared, across these different cell a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 119 publications
(164 reference statements)
3
64
0
Order By: Relevance
“…We demonstrate here several fetal alterations that potentially predispose to the early adult impaired cardiac ventricular dysfunction previously reported (11,14,85). Numerous studies establish that mitochondrial alterations produced by gestational exposure persist into adulthood or across generations (20).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…We demonstrate here several fetal alterations that potentially predispose to the early adult impaired cardiac ventricular dysfunction previously reported (11,14,85). Numerous studies establish that mitochondrial alterations produced by gestational exposure persist into adulthood or across generations (20).…”
Section: Discussionsupporting
confidence: 60%
“…The dysfunction is similar to human cardiac failure with preserved ejection fraction. Notwithstanding the strong association between poor maternal nutrition and adverse fetal and life-course cardiac programming, direct and causal effects on fetal heart mitochondrial biology remain uninvestigated (19,20). Disturbance of the energy transformation process is a prime feature of heart failure in subjects with cardiomyopathy (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental data for zebra finches ( Taeniopygia guttata ) indicated that prior exposure of adults to simulated heat waves had little effect on their subsequent physiology ( Cooper et al, 2020b ). However, early life experiences can prepare subcellular and whole-animal phenotypes for subsequent thermal conditions ( DuRant et al, 2013 ; Jonsson and Jonsson, 2014 ; Hepp et al, 2015 ; Gyllenhammer et al, 2020 ; Koch et al, 2021 ); these developmental effects can be as substantial as inter-population differences ( Tracy and Walsberg, 2001 ). Physiological consequences of heat waves experienced during post-natal growth by altricial birds have received little attention, despite this being the period when thermoregulation develops.…”
Section: Introductionmentioning
confidence: 99%
“…We measured metabolic rate (MR; measured as oxygen consumption, VO 2 ), body temperature (T b ), and evaporative water loss (EWL) and calculated wet thermal conductance (C wet ) and relative water economy (RWE), at three thermoregulatory stages (ectothermic, poikilothermic, and endothermic; Sirsat et al, 2016a ). We also measured the nestlings’ growth rate, and assessed mitochondrial function of red blood cells once they reached adulthood (e.g., early-life programming effects; Gyllenhammer et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature shows how [Ca 2+ ]i and energy availability also play an important role in embryonic development, mitosis and how alterations in these processes can have severe consequences and result in several diseases [41][42][43] . It is therefore not surprising that, by modulating [Ca 2+ ]i and enhancing energy production, GA and DL have such an effect not only in these cellular functions but also rescuing pathological conditions such as neurological diseases.…”
Section: Discussionmentioning
confidence: 99%